Bank competition and ECB's monetary policy - Bagliano, Fabio C.; Dalmazzo, Alberto; Marini, Giancarlo (Journal of Banking & Finance, 2000)
In a model of oligopolistic competition in the banking sector, we analyse how the monetary policy rule chosen by the Central Bank can influence the incentive of banks to set high interest rates on loans over the business cycle. We exploit the basic model to investigate the potential impact of EMU implementation on collusion among banks. In particular, we consider the possible effects of the European Central Bank's policy criteria with regard to the cost of credit in national markets.